Bioactive constituents from the leaves of Quercus phillyraeoides A. Gray for α-glucosidase inhibitor activity with concurrent antioxidant activity - Anastasia Wheni Indrianingsih; Sanro Tachibana (Food Science and Human Wellness)
Several α-glucosidase inhibitory constituents were isolated from the methanolic extract of the leaves of Quercus phillyraeoides A. Gray (Q. phillyraeoides) using a bioassay-guided fractionation technique. Further separation and purification of the methanol-soluble fraction led to the isolation of constituents with moderate and strong inhibitory activities against α-glucosidase: β-sitosterol-d-glucoside (1) and condensed tannin fractions (2, 3, 4, 5, and 6). Compound 1 and fractions 2–6 had inhibitory concentration (IC50) values against α-glucosidase from Saccharomyces cerevisiae of 118.8, 2.79, 2.78, 3.10, 2.60, and 3.14 μg/mL, respectively, while quercetin as the standard had an IC50 value of 4.80 μg/mL. Furthermore, the significant antioxidant activities were evaluated using several assays, such as the DPPH radical scavenging, hydrogen peroxide radical scavenging, reducing power, and β-carotene-linoleate bleaching assays, and the results suggested that the isolated constituents showed their possible application for treating the hyperglycemia-induced oxidative stress. The results of the present study showed the potential of Q. phillyraeoides as a rich source of natural antidiabetic medicine.